Community Stigma in Lampung Province Towards Individuals with Hearing Impairments - Azzahra, Aulia; Devita, Dela; Sani, Yulvia (Universitas Sang Bumi Ruwa Jurai, 2025)
This study aims to investigates the stigma experienced by individuals with hearing impairments in Lampung Province. Employing a descriptive quantitative method with a survey approach, the research involved 400 respondents, whose sample size was determined using the Slovin formula. Cluster random sampling was utilized to select participants from five regencies and two cities within Lampung Province, namely the regencies of South Lampung, East Lampung, West Lampung, North Lampung, and Central Lampung, as well as the cities of Bandar Lampung and Metro. The research instrument was an attitude questionnaire comprising 58 statement items, measured on a 4-point Likert scale. These items included both favorable and unfavorable statements, structured around Link and Phelan's five dimensions of stigma. Validity and reliability tests were conducted using SPSS version 25.0. Validity results indicated a correlation value of r more than 0.30 for all items, and the reliability coefficient was 0.736. The findings reveal that the majority of respondents (253 individuals, or 63 percent) exhibited a Category 2 (moderate) level of stigma towards individuals with hearing impairments. Conversely, 81 respondents (20 percent) were in Category 1 (low), and 66 respondents (17 percent) were in Category 3 (high). This study recommends the development of continuous education and public socialization programs that target stigma reduction, promote inclusive communication practices, and encourage community engagement. Such efforts are expected to foster a more inclusive and empathetic social environment for individuals with hearing impairments in Lampung Province.